Correlation of gestational age and age at death in sudden infant death syndrome: another pointer to the role of critical developmental period? - Malgorzata Habich; Piotr Zielenkiewicz; Leszek Paczek; Pawel Szczesny (BMC Pediatrics, 2024)
Abstract Background Filiano and Kinney proposed a triple-risk model for the sudden infant death syndrome (SIDS) that involves the intersection of three risks: (1) a vulnerable infant, (2) a critical developmental period in homeostatic control, and (3) an exogenous stressor(s). The primary evidence for the role of a critical developmental period in SIDS etiology is the peak of cases around the third month of life. Independently, several studies pointed to correlation between gestational age and age at death in SIDS, but used that to assess the SIDS risk for preterm infants, ignoring further ramifications. Methods We did a detailed analysis of CDC data spanning over two decades (1983–2011). We focused not only on the correlation between two age variables (gestational and age at death), but also on the possibility of misdiagnosis. Also, we attempted to account for potential biases in the data induced by the ICD-9/ICD-190 transition or the “Back to Sleep” campaign. Results The peak of deaths in the third month of life, that was the main argument for the role of the critical development period, wasn’t unique to SIDS. However, we confirmed an almost linear and negative correlation between gestational age and the week of death due to SIDS. This pattern (slope of correlation < 0 and significance of correlation p < 0.05) is characteristic of SIDS among all diseases analyzed in the study. Conclusions We interpret the results as the evidence of the role of the critical development period in SIDS etiology. Possibly more attention in the future research should be put to theories that are based on homeostatic control.